Les comptes rendus des débats parlementaires dans le Moniteur universel pendant la période révolutionnaire (mars 1790) : donner à comprendre les échanges politiques à l’Assemblée nationale - Caroline Facq-Mellet (Corela)
This article examines the didactic and educational function of the reports of parliamentary sessions published in the Moniteur universel in the general context of the "media revolution" (Popkin 2011) that France experienced from 1789 onwards. During this period, newspapers contributed to the citizenship education of the French people. The hypothesis we formulate here is that the reports of parliamentary debates, published in this newspaper, contribute to the training of the citizen: indeed, in these texts, the representation of political debates cannot be dissociated from a reading guide for novice citizens, discovering through these writings a new political practice. As a kind of "addressed" discourse, the report of parliamentary debates adapts to this new readership, providing an understanding of the representation of political exchanges in the Assembly. The specific aim of the article is to show that, among all the forms of textual guidance, the choice of forms of representation of another discourse, as well as their arrangement, contribute to making sense of the representation of exchanges at the Assembly.